The Norwegian national trauma registry: development process and essential data insights - Kjetil Gorseth Ringdal; Kjetil Tengesdal Holm; Olav Røise (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Background Understanding trauma epidemiology, patient demographics, injury characteristics, and outcomes is essential for optimising trauma systems. The Norwegian Trauma Registry (NTR) monitors and improves the Norwegian Trauma System, setting care standards and overseeing system development. The registry was officially recognised as a national register in 2013. This study outlines the establishment of the population-based national registry and provides an overview of selected data. Methods Norway’s trauma system includes trauma centres, acute care hospitals, and prehospital services. The registry collects injury details, clinical outcomes, and patient experiences. Local NTR databases that are linked to a central database are maintained at each hospital, and only certified data registrars can enter and validate data. This enables data linkages across hospitals. The NTR includes potentially severely injured patients but also includes undertriaged patients (defined as severely injured patients who are not met by a trauma team activation upon hospital arrival). Descriptive statistics were used to analyse data from trauma patients registered between 2015 and 2023. Patient-Reported Outcome Measures (PROMs) from 2022 were also assessed. Results From 2015 to 2023, 78 275 trauma patients were recorded, with annual patient inclusion rising from 7586 in 2015 to 9759 in 2023. All 38 Norwegian hospitals contributed data in 2023. Median age was 41 years (IQR: 21–62), and 66.5% were men. The highest injury rate was among those aged 15–24 years. Penetrating injuries accounted for 4.6% of cases. Severely injured patients with New Injury Severity Score (NISS) ≥ 16 totalled 16 678 (21.3%), while 10 509 (13.4%) had an Injury Severity Score (ISS) ≥ 16. Polytrauma was identified in 3783 (4.9%) of patients using the Newcastle definition and in 2508 (3.2%) patients using the Berlin definition. In 2023, a trauma team was activated for 8731(89.4%) patients recorded in the registry. PROMs data from 2022 showed that 47.2% (1018/2157) of the patients reported anxiety or depression 12 months post-injury. Among those without physical injuries, 8.0% (11/138) were out of work or education. Of the severely injured patients (NISS ≥ 16) who were employed or in education prior to the injury, 26.4% (83/314) had not returned to work or education after 12 months. Conclusions The Norwegian Trauma Registry has been successfully implemented in all trauma hospitals in Norway, enabling comprehensive data collection to support trauma care improvements and research.